Development of a technology for the production of germinated flaxseed using plasma-chemically activated aqueous solutions - Kovaliova, Olena; Vasylieva, Natalia; Stankevych, Serhii; Zabrodina, Inna; Mandych, Oleksandra; Hontar, Tatyana; Haliasnyi, Ivan; Kotliar, Oleh; Yanchyk, Oleksandr; Bogatov, Oleg (PC Тесhnology сеntеr, 2023)
The result of the research is the development of a technology for the production of germinated flaxseed using plasma-chemically activated aqueous solutions. The object of research was flaxseed. An urgent technological problem is the intensification of the bioactivation process of flaxseed and its effective disinfection. The expediency of using plasma-chemically activated aqueous solutions as an intensifier of the process of flaxseed germination and an effective disinfectant of food raw materials was experimentally proven. It is shown that the use of plasma-chemical activation of process solutions not only accelerates flaxseed germination, but also contributes to a more active accumulation of biologically valuable components in flax raw materials. The composition of flaxseed as a raw material derivative was analyzed. Germinated flaxseed, which is considered a high-value component of food products, was studied separately. An increase in the moisture content of flaxseed during the soaking process by 0.7–1.7 % was recorded. Seedling development increases by 2–9 mm. The germination energy and capacity increase by 5–12 %. The biomass of germinated seeds increases by 39–56 %. In the process of germination, the content of proteins in flaxseed increases from 21.88 to 23.71 %, reducing sugars from 2.37 to 4.02 %. The total content of amino acids increases from 3.64 to 10.38 % compared to the control, and 10 times compared to the raw material. A significant accumulation of vitamins was noted: B1, B2, B3, B5, B6, B7, B9, C, E. In addition, plasma-chemically activated solutions effectively disinfect germinated flaxseed. The technology can be applied in the production of enrichment components of food products. The developed technology will receive special attention in the production of functional food products
Keywords: flaxseed; plasma-chemical activation; germination; germinated seeds; biologically active substances